2020
DOI: 10.1103/physrevd.102.014008
|View full text |Cite
|
Sign up to set email alerts
|

Rapidity loss, spin, and angular asymmetries in the scattering of a quark from the color field of a proton or nucleus

Abstract: We calculate the helicity amplitudes for scattering of a quark from both large and small x gluons of a target proton or nucleus using spinor helicity formalism. We show that scattering from large x gluons of the target results in nonzero spin asymmetry at intermediate p t as well as rapidity loss of the projectile quark. We comment on how this can also generate angular asymmetries in particle production in high energy collisions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…A similar idea is also proposed in [66] where a formulation for unintegrated gluon distributions that interpolates between the small and moderate values of energy is studied. A different approach based on exchanging longitudinal momentum during the scattering to go beyond eikonal accuracy is pursued in [67][68][69]. Also, NEik corrections are computed in the context of soft gluon exponentiation for example in [70][71][72].…”
mentioning
confidence: 99%
“…A similar idea is also proposed in [66] where a formulation for unintegrated gluon distributions that interpolates between the small and moderate values of energy is studied. A different approach based on exchanging longitudinal momentum during the scattering to go beyond eikonal accuracy is pursued in [67][68][69]. Also, NEik corrections are computed in the context of soft gluon exponentiation for example in [70][71][72].…”
mentioning
confidence: 99%
“…In [4] we calculated the cross section for scattering of a quark from both small and large gluons of the target. Specifically, we considered scattering of a projectile parton of a given helicity [7] on the unpolarized target and showed that inclusion of large parton of the target leads to a spin asymmetry in the production cross section.…”
Section: Pos(hardprobes2020)188mentioning
confidence: 99%
“…To remedy this it is essential to generalize the CGC formalism to include large partons of the target. In [4] we proposed a new formalism which includes scattering from both small and large partons of the target.…”
Section: Introductionmentioning
confidence: 99%
“…(47) and (44) into Eq. (14), performing the substitution (17), and integrating out r with the help of the delta function yields [cf. Eq.…”
Section: Estimates Of the Asymmetry: Subleading N Cmentioning
confidence: 99%
“…The recent decade and a half saw a surge of research activity at the intersection of small-x and spin physics in quantum chromodynamics (QCD) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Topics receiving attention include both the longitudinal [10,11,15,[18][19][20][21][22][23] and transverse [7,[24][25][26][27][28][29][30] spin physics of the proton.…”
Section: Introductionmentioning
confidence: 99%